Primary scalp alopecia: new histopathological tools, new concepts and a practical guide to diagnosis. (28th October 2016) - Kolivras, Athanassios; Thompson, Curtis
Abstract : The diagnosis of primary scalp alopecia remains one of the most challenging fields in dermatopathology. In this review, we would like to connect the established classification of primary alopecia into scarring (cicatricial) and non‐scarring (non‐cicatricial) with current concepts. We introduce a simplified pathway for the diagnosis of the most common causes of alopecia, including a discussion of tissue processing techniques and use of immunohistochemistry.